ANDRAGOGY IN NURSING EDUCATION - Rosita Saupe; Magda Rojas Yoshioca; Ana Lúcia Gawlinski de Arruda (Universidade Federal do Paraná, 1998)
Andragogy is a little known word, meanig the science of adult education. Its principies, presuppositions and methodological proposal are presented as a possibility in adult education, covering health-related questions in a way frequently developed by nurses.